Typification of the name Eryngium siculum (Apiaceae) - Scafidi, Filippo; Ferraro, Valeria; Di Gristina, Emilio (Phytotaxa, 2020)
As part of an ongoing study on the names of vascular plants described from Sicily (e.g., Di Gristina et al. 2012, Domina et al. 2014, 2016, Di Gristina et al. 2017, Domina et al. 2017a, 2017b, Scafidi & Domina 2019, Di Gristina et al. 2020), a nomenclature study of the name Eryngium siculum Lojacono-Pojero (1906: 294) (Apiaceae Lindl.), which appears to be yet untypified (see Domina et al. 2014, Peruzzi et al. 2015), is here presented. The present study, which deals with the untypified name Eryngium siculum Lojacono-Pojero (1906: 294), falls within the researches promoted by the Italian Botanical Society aimed to recognize and typify all the taxa described from Italy, in order to increase their systematic knowledge and promote further studies (Peruzzi et al. 2015, Brundu et al. 2017, Peruzzi et al. 2019).